Marine Oil Spills 2018 - Fingas, Merv (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The mitigation of oil spills is an important facet of environmental protection. Understanding oil spills is a first step toward preventing and minimizing their damage to the environment. This compilation presents several of the current studies related to such an understanding of oil spills and the environment.<false,>This book is a compilation of 14 papers presenting new developments in the field of oil spills, giving insight into the rapidly changing world of oil spill studies and technology. The 14 papers included cover topics varying from risk analysis to oil spill remote sensing. Broadly categorized, included are six papers on modeling, four papers on remote sensing, three papers on risk assessment, and one paper on oil spill countermeasures. Each paper presents a unique insight into a facet of oil spill research and technology. The authors of these papers represent many different countries and affiliations around the world.